CORM-2 Pretreatment Attenuates Inflammation-mediated Islet Dysfunction. (4th May 2020) - Cai, Xiang-Heng; Wang, Guan-Qiao; Liang, Rui; Wang, Le; Liu, Teng-Li; Zou, Jia-Qi; Liu, Na; Liu, Yan; Wang, Shu-Sen; Shen, Zhong-Yang
During the process of human islet isolation a cascade of stressful events are triggered and negatively influence islet yield, viability, and function, including the production of proinflammatory cytokines and activation of apoptosis. Carbon monoxide-releasing molecule 2 (CORM-2) is a donor of carbon monoxide (CO) and can release CO spontaneously. Accumulating studies suggest that CORM-2 exerts cytoprotective and anti-inflammatory properties. However, the effect of CORM-2 on islet isolation is still unclear. In this study, we found that CORM-2 pretreatment significantly decreased the expression of critical inflammatory genes, including tissue factor, intercellular adhesion molecule-1, chemokine ( C-C motif ) ligand 2, C-X-C motif chemokine 10, Toll-like receptor 4, interleukin-1β, interleukin-6, and tumor necrosis factor-α ( TNF-α ). The isolated islets of the CORM-2 pretreatment group showed reduced apoptotic rate, improved viability, and higher glucose-stimulated insulin secretion, and functional gene expression in comparison to control group. Importantly, CORM-2 pretreatment prevented the impairment caused by TNF-α, evidenced by the improved glucose-stimulated index and transplantation outcomes. The present study demonstrated the anti-inflammatory property of CORM-2 during human islet isolation, and we suggest that CORM-2 pretreatment is an appealing treatment to mitigate inflammation-mediated islet dysfunction during isolation and culture ex vivo and to preserve long-term islet survival and function.